Work Stress among School Teachers: A Systematic Literature Review - Kavitha B.; Jacintha Veigas; Nandini Mannadath (Social Medicine)
Teachers at higher secondary schools work with teenagers as their students. Students' stress levels rise during adolescence, which can be a time of anxiety, tension, emotional storms, and conflict. Teachers experience excessive stress as a result, which impacts every part of their lives 1 . The goal of this review is to learn more about the level of stress that educators encounter, how it affects their performance at work, and th e coping strategies that they use to manage it. The researcher thoroughly studied the previous research literature from journals, research articles, theses, and dissertations to identify 21 relevant studies , conducted in India and abroad. Purposive sampli ng was used and a modified checklist of CASP (Critical Appraisal Skills Programs) was used to analyze the extracted data. It was discovered through a review of earlier studies that secondary school teachers experience moderate to severe levels of work rela ted stress. Big class sizes, issues with controlling student behavior, a lack of professional development opportunities, a lack of staff interaction and time for curriculum discussions, inadequate pay, a lack of intrinsic satisfact ion, and a s hortage of us eful teaching aids all emerged as sources of stress , which also affected their performance . To deal with their stress, t eachers used the coping strategies of sleeping, w atching TV, talking wit h friends, listening to music, shopping, and t raveling to places of natural beauty. This systematic review highlights the need to reduce teacher stress because stressed teachers are less able to instruct students effectively and to create an environment that makes learning c hallenging and engaging